2020
DOI: 10.3389/fphys.2020.01072
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Influence of Hypobaria on Heart Rate Variability in Hypoxia and Normoxia

Abstract: Introduction: The present study evaluated the putative effect of hypobaria on resting HRV in normoxia and hypoxia. Methods: Fifteen young pilot trainees were exposed to five different conditions in a randomized order: normobaric normoxia (NN, P B = 726 ± 5 mmHg, F I O 2 = 20.9%), hypobaric normoxia (HN, P B = 380 ± 6 mmHg, F I O 2 ∼ =40%), normobaric hypoxia (NH, P B = 725 ± 4 mmHg, F I O 2 ∼ =11%); and hypobaric hypoxia (HH at 3000 and 5500 m, HH3000 and HH5500, P B = 525 ± 6 and 380 ± 8 mmHg, respectively, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Our study confirmed a higher oxygen saturation in NH vs. HH after 24 h of hypoxic exposure. This is already well described for shorter exposition times ( Aebi et al, 2020 ; Debevec et al, 2020 ) and logically was also already reported in the three support experiments of the present study. However, the latter was still debated for exposures longer than 8 h ( Coppel et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study confirmed a higher oxygen saturation in NH vs. HH after 24 h of hypoxic exposure. This is already well described for shorter exposition times ( Aebi et al, 2020 ; Debevec et al, 2020 ) and logically was also already reported in the three support experiments of the present study. However, the latter was still debated for exposures longer than 8 h ( Coppel et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, HRV could be analyzed similarly in NH and HH conditions. Furthermore, together with previous results on acute exposures ( Aebi et al, 2020 ), it forms a reliable basis for a similar interpretation of HRV in NH and HH during both acute and long hypoxic exposures.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations